Primary anaplastic T-cell lymphoma of the omentum presenting as small bowel obstruction and complicated with Massilia timonae infection: a case report - Sarmad Pirzada; Ibrahim Zahid; Ali Abbas Mankani; Muhammad Zain Farooq; Wesam M. Frandah (Journal of Medical Case Reports)
Abstract Background Anaplastic large-cell lymphoma primarily involving the omentum is an extremely rare entity with variable clinical presentation. Owing to its rarity and nonspecific clinical manifestation, omental T-cell lymphoma is often diagnosed at a later stage, riddled with complications. While imaging modalities such as computed tomography scan can help a physician reach a diagnosis, cases that present with complications may require a multidisciplinary approach that combines surgical exploration along with consultation from Oncology. Case presentation We hereby report a rare case of a 66-year-old African American male patient who presented to the emergency department with complaints of acute gastrointestinal obstruction. A computed tomography scan of the abdomen and pelvis revealed evidence of an internal hernia and surgical exploration revealed a hemorrhagic and infarcted omentum. Biopsies along with immunophenotypic studies confirmed the diagnosis of anaplastic T-cell lymphoma of the omentum complicated by Massilia timonae infection. Conclusion The case highlights the significance of considering lymphoma, although rare, as a differential in a patient who presents with small bowel obstruction and the importance of investigating for malignancy for early diagnosis and treatment of primary omental lymphomas, before complications develop.